Dengue vectors in Africa: A review. Issue 5 (May 2022) - Diallo, Diawo; Diouf, Babacar; Gaye, Alioune; NDiaye, El hadji; Sene, Ndeye Marie; Dia, Ibrahima; Diallo, Mawlouth
Abstract: Dengue fever is a mosquito-borne-disease of growing public health importance in Africa. The continuous increase of number and frequency of outbreaks of dengue fever, especially in urban area in Africa underline the need to review the current data available on vectors involved in dengue virus transmission in Africa. Here, we summarized the available data on vectors involved in the transmission of dengue virus in the sylvatic and urban environments, vertical transmission, vector competence studies, and vector control strategies used in Africa. The virus was isolated mainly from Aedes furcifer, Ae. luteocephalus, and Ae. taylori in the sylvatic environment and from Ae. aegypti and Ae. albopictus in the urban areas. Prospective and urgently needed studies on vectors biology, behavior, and alternative control strategies are suggested. Graphical abstract: Image 1 Abstract : Dengue; Mosquito vectors; Sylvatic; Urban; Africa.